ESTIMATION OF GENETIC PARAMETERS AND GENE ACTION FOR YIELD OF SEED COTTON AND LINT PERCENTAGE IN GOSSYPIUM HIRSUTUM L. - Murtaza, Naveed; Khan, Azhar Ali; Qayyum, Abdul (Journal of Research (Science), 2002)
Gene action and genetic parameters for yield of seed cotton and lint percentage were studied in an eight parent diallel cross of upland cotton, which revealed that both additive and dominance components had prepondence in the inheritance of these characters. Asymmetrical distributions of dominant and recessive genes in the parents were observed. Low to moderate estimates of narrow sense heritability was obtained for both the characters.